2011
DOI: 10.4100/jhse.2011.62.23
|View full text |Cite
|
Sign up to set email alerts
|

A study of anthropometric profile of indian inter-university male cricketers

Shyamal Koley

Abstract: Koley S. A study of anthropometric profile of indian inter-university male cricketers. J. Hum. Sport Exerc. Vol. 6, No. 2, pp. 427-435, 2011. The purpose of this study was of two-fold, firstly, to evaluate the anthropometric profile of Indian inter-university cricketers and, secondly, to search the correlations among the anthropometric characteristics studied (if any). To serve this purpose, twelve anthropometric characteristics were taken on purposively selected 98 Indian inter-university (nine Indian univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…The specific anthropometric and fitness characteristics such as stature, body mass, physical strengths, dash sprint and jumping are associated with the good performance of players (Ackland, Ong, Kerr, & Ridge, 2003;Mohamed, et al, 2009;Koley, 2011). It was concluded the stronger anthropometric and fitness characteristics exhibit good performance during domestic and international competitions (Stuelcken, Pyne, & Sinclair, 2007;Koley, 2011). It is was also reported the longer arms provide mechanical advantages to increase the batting and bowling performance of the cricket players (Aruparayil & Chattopadhyay, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific anthropometric and fitness characteristics such as stature, body mass, physical strengths, dash sprint and jumping are associated with the good performance of players (Ackland, Ong, Kerr, & Ridge, 2003;Mohamed, et al, 2009;Koley, 2011). It was concluded the stronger anthropometric and fitness characteristics exhibit good performance during domestic and international competitions (Stuelcken, Pyne, & Sinclair, 2007;Koley, 2011). It is was also reported the longer arms provide mechanical advantages to increase the batting and bowling performance of the cricket players (Aruparayil & Chattopadhyay, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have examined the anthropometric measures of district and state cricket players (Koley & Yadav, 2009), district players (Koley, Kumar & Shadagopan, 2012), and university cricket players and sedentary students (Koley, 2011). It was reported that South African university cricketers were superior in their physical characteristics than sedentary subjects (Stretch & Buys, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It was earlier reported that handgrip strength had strong correlations with various anthropometric characteristics ( Bamaç, B., Colak, T., Özbek, A., Yenigün, N., Çolak, S., & Bamaç, Y, 2003;Koley, Singh & Kaur, 2010;Koley & Kaur, 2011).…”
Section: Discusion and Conclusionmentioning
confidence: 99%
“…Many scientist have done a research on anthropometric parameters of cricket players and HGS in them. [4,5] Contemporary sports science is designed to improve the performance of elite players and to discover talents as precisely as possible. Percentage of lean body mass is different in cricket and football.…”
Section: Introductionmentioning
confidence: 99%